UNDERSTANDING THE MOTIVES AND TYPIFICATIONS OF YOUTUBER GAMING ON SOCIAL MEDIA: A PHENOMENOLOGY STUDY - Afdal Makkuraga Putra; Andreas Dion Anggoro; Sofia Aunul; Riza Darma Putra (ASPIRATION Journal, 2021)
This study aims to analyze the motives and typify of Youtuber Mobile Legend Bang Bang (MLBB). This study uses Alfred Schutz's theory of phenomenology with a constructivist paradigm and phenomenological methods. To collect data, it was done by interviewing 7 informants and observing the informants' YouTube channel. The results of the research and data analysis show that there are several "motives because" MLBB players become gaming youtubers driven by 2 things, namely hobbies or fun and having free time. Meanwhile, the "motive for" which was found was related to 3 things. First, it relates to the desire of MLBB players to share their knowledge and playing skills. Second, about the MLBB players that many people want to watch. Third, it relates to the desire of MLBB players who want to be recognized as great or professional in playing. Based on these motives, this study categorizes 3 types of YouTubers MLBB in forming their identity on YouTube, namely Casual YouTubers, Sharing YouTubers, and Achieved YouTubers.